Zpracování multimediálních dat v heterogenním distribuovaném prostředí - Kajan, Rudolf (Vysoké učení technické v Brně. Fakulta informačních technologií)
Pervasive computing sa zameriava odstránenie zložitostí pri interakcii s výpočtovou technikou a zvýšenie efektivity pri jej každodennom používaní. Ale i po viac ako 15 rokoch od sformulovania hlavných cieľov Pervasive computingu existujú aspekty interakcie ktoré stále nie sú súčasťou užívateľskej skúsenosti s dnešnou technológiou. Bezproblémová integrácia s prostredím vedúca k technologickej neviditeľnosti, alebo interakcia naprieč rôznymi zariadeniami predstavujú stále veľkú výzvu. Hlavným cieľom tejto práce je prispieť k tomu, aby sa ciele Pervasive computingu priblížili k realizovaniu tým, že predstavíme spôsob intuitívneho zdieľania informácií medzi osobným a verejne umiestneným zariadením. Predstavili sme tri interakčné techniky, ktoré podporujú intuitívnu výmenu obsahu medzi osobným zariadením a zdieľaným displejom. Tieto techniky sú založené na prenose videa, rozšírenej realite a analýze pohľadových dát. Okrem interakčných techník sme tiež predstavili mechanizmus pre získavanie, prenos a rekonštrukciu aplikačného stavu na cieľovom zariadení.

Ubiquitous computing, a paradigm in which the processing of information is linked with each activity or object as encountered, was proposed by Mark Weiser as the next era for interacting with computers. Its goal is to enable people to interact with devices more naturally and casually in ways that suit whatever location or context they find themselves in. Ubiquitous computing focuses on learning by removing the complexity of computing and increases efficiency while using computing for different daily activities. But after more than 15 years since Weiser formulated these goals, several aspects of ubiquitous computing are still not a part of user experience with today’s technology. Seamless integration with environment leading to technological invisibility or user interaction spanning across multiple devices pose still a great challenge. The main goal of our work is to make a step towards making the idea of ubiquitous computing a reality by addressing the question about intuitive information sharing between a personal device and a situated display. We have developed three interaction techniques which support unobtrusive content exchange between touch-enabled personal device and a large display - whether it is shared-private or public. These techniques are based on video streams, augmented reality, and analysis of gaze data. Besides the interaction techniques, we also present a framework for real-time application state acquisition and reconstruction on target platform. We report on user studies focused on the usability of our prototypes and a system performance evaluations. Our experiments were formed around real-life scenarios which are commonly experienced throughout the day. For interactions based on video streams, the results indicate that our techniques outperform the existing solutions: the localization and task migration is done in real time on a midlevel cellphone; the localization is reliable even for different observation angles and for cluttered screen content. Our technique based on gaze analysis goes even further by allowing for modeling of implicit user preferences through gaze data, while being accurate and unobtrusive.
Multimedia Data Processing in Heterogeneous Distributed Environment
Keywords: Sledování pohledu HCI Všudypřítomné displeje Multimodální interakce; Eye tracking Pervasive displays HCI Multi modal interaction